2020
DOI: 10.1177/0018720820964149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Driver Features for Cognitive Distraction Detection and Validation in Manual and Level 2 Automated Driving

Abstract: Objective This study aimed to investigate the impacts of feature selection on driver cognitive distraction (CD) detection and validation in real-world nonautomated and Level 2 automated driving scenarios. Background Real-time driver state monitoring is critical to promote road user safety. Method Twenty-four participants were recruited to drive a Tesla Model S in manual and Autopilot modes on the highway while engaging in the N-back task. In each driving mode, CD was classified by the random forest algorithm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…This is a critical aspect of gaze behaviour to examine as a lack of scanning during phase(s) of flight that require continuous monitoring of flight parameters (i.e., landing) and aircraft state via gauges inside the cockpit can result in disastrous consequences should an unexpected/hazardous event occur. This phenomenon was similarly reported in driving simulation studies that found that the higher proportion of dwell time allocated to the center of the road and a reduction in gaze dispersion were associated with driver distraction, reduced hazardous event detection, and increased driver cognitive load ( 41 ; 58 ; 60 ; 61 ). The increased cognitive tunneling findings seemingly contradict the increase in final approach SGE and GTE during difficult trials.…”
Section: Discussionsupporting
confidence: 71%
“…This is a critical aspect of gaze behaviour to examine as a lack of scanning during phase(s) of flight that require continuous monitoring of flight parameters (i.e., landing) and aircraft state via gauges inside the cockpit can result in disastrous consequences should an unexpected/hazardous event occur. This phenomenon was similarly reported in driving simulation studies that found that the higher proportion of dwell time allocated to the center of the road and a reduction in gaze dispersion were associated with driver distraction, reduced hazardous event detection, and increased driver cognitive load ( 41 ; 58 ; 60 ; 61 ). The increased cognitive tunneling findings seemingly contradict the increase in final approach SGE and GTE during difficult trials.…”
Section: Discussionsupporting
confidence: 71%
“…This performance is on par with current state-of-the-art machine learning methods, such as from Yang et al 2020 [ 22 ], who developed three models for detecting cognitive distraction with accuracies around 80%. Similarly, the AIDE EU project states that for the purpose of informing other in-vehicle systems, a distraction detection accuracy of 70% is sufficient and 85% is good.…”
Section: Study 1: Investigation Of Temporal Regularity Reduction and ...mentioning
confidence: 58%
“…Abosaq et al [ 65 ] proposed a customized CNN model ( Figure 5 ) to recognize normal and abnormal driver actions (including driver smoking, driver eating, driver drinking, driver calling, and driver normal) from driver videos, and achieved 95% accuracy on the prepared testing dataset. Yang et al [ 66 ] investigated the impacts of feature selection on driver cognitive distraction detection and validation in real-world non-automated and Level 2 automated driving scenarios. A Mobileye sensor recorded vehicle performance while two Logitech webcams and a forward-facing camera collected video data of 24 drivers (12 males and 12 females with ages 22–68) and roadway.…”
Section: Driver State Monitoringmentioning
confidence: 99%